Hmg1 mutations in Aspergillus fumigatus and their contribution to triazole susceptibility. (21st May 2021) - Arai, Teppei; Umeyama, Takashi; Majima, Hidetaka; Inukai, Tatsuya; Watanabe, Akira; Miyazaki, Yoshitsugu; Kamei, Katsuhiko
Abstract: Triazole-resistant Aspergillus fumigatus is a global health concern. In general, each triazole resistance pattern caused by the specified amino acid substitution of Cyp51A has a typical pattern depending on the mutation site. We evaluated the contribution of both Cyp51A and Hmg1 mutations to atypical triazole resistance in A. fumigatus . We used clinical triazole-resistant A. fumigatus strains collected in Japan and investigated the sequences of cyp51A and hmg1 genes. To delineate the association between the hmg1 mutation and atypical triazole resistance, the mutant hmg1 alleles in clinical multi-azole resistant strains were replaced with the wild-type hmg1 allele by CRISPR/Cas9 system. In our study, the combination of Cyp51A mutation and Hmg1 mutation was shown to additively contribute to triazole resistance. We also demonstrated that the triazole resistance conferred by the Hmg1 mutation showed a different pattern depending on the mutation site, similar to the Cyp51A mutation. Our results indicate that focusing on the phenotypes of multiple genes is essential to clarify the overall picture of the triazole resistance mechanism of A. fumigatus . Lay Summary: The number of triazole-resistant Aspergillus fumigatus is increasing. We confirmed thatmutation in a hydroxymethylglutaryl-CoA reductase (Hmg1) in the fungus contributesto the resistance separately from Cyp51A mutation, and that susceptibility patterns aredifferent based on mutation site.